(untitled) (Northern International Medical College Journal, 2015)
Objective : To identify etiology of neonatal hyperbilirubinaemia requiring Exchange Transfusion (ET) and to see the complications of ET and its outcomes. Methods : This prospective study was done in a tertiary hospital. Total 39 admitted newborn babies with hyperbilirubinaemia who required exchange transfusion were enrolled and all information regarding etiology of jaundice, laboratory investigations, complications and outcomes of cases were documented and analyzed. Results : During one year of study period ET was done in 39 neonates. Among them 16 (41%) cases were male and 23(59%) were female. Fifteen (38%) babies were preterm and 24(62%) babies were term. Fifteen (38%) babies were preterm low birth weight (PLBW) with or without septicaemia as comorbidity. Twelve (31%) cases had only hyperbilirubinaemia. Rh-incompitability was seen in 17 (44%), ABO incompitability in 15(38%) cases and unknown cause in 7(18%) neonates. Common complications seen were hypoglycaemia in 7(18%) and thrombocytopenia in 6(15%) neonates. Two (5%) neonates who died had comorbidity. Conclusion : Exchange transfusion is required mostly in Rh incompitability and common complications of ET were hypoglycaemia and thrombocytopenia. Northern International Medical College Journal Vol.6(2) 2015: 70-72